Some considerations on the principles of the Cognitive Theory of Multimedia Learning for instructional video design for the elderly (Research, Society and Development, 2022)
The COVID-19 pandemic exposed that the field of education has been using indiscriminately instructional videos. The starting point is evident, a lack of careful design, and in that scenario, the Cognitive Theory of Multimedia Learning may play a significant role. The rationale of this study is that the elderly, as the targeted audience, might have cognitive decay, hearing loss, or eyesight decline, which might impact the principles of the Cognitive Theory of Multimedia Learning. This work is an analysis of the evidence that supports or not these cognitive processing principles based on previous literature, with an additional investigation of the literature for the Brazilian scientific journals market. Then, some processing principles of this theory are evaluated for instructional video design for the elderly. The main results summarize that only instructional material directly related to the key learning goal should be included, that important information should be highlighted to learners, that longer videos should be broken into meaningful parts, and that redundancy in instructional videos for the elderly should be investigated considering their specificities.